Evaluation of lightweight aggregates in chip seal - Islam, Md Shahidul (Kansas State University, 2010)
Pavement preservation by adopting low-cost maintenance techniques is increasing among transportation agencies day by day. Chip seal, also known as seal coat, is widely used as a low-cost, thin surface treatment in preventive maintenance of asphalt pavements in many states, including Kansas. Loosening of aggregate particles from chip-sealed pavement and associated windshield damage to vehicles is a common problem. Thus the Kansas Department of Transportation (KDOT) uses lightweight aggregates as cover materials for chip seals. Although this has decreased windshield damage problems extensive chip loss on seal-coated pavements in the state has been reported. In this study, lightweight aggregates along with polymer-modified asphalt emulsion were used to determine proper aggregate and emulsion application rates to minimize chip loss in chip seals. Again, lightweight aggregates were studied in the laboratory to determine the effect of moisture content and electrical charge on chip loss. Evaluation of chip seal was performed by statistical analysis based on rutting potential, chip embedment, and retention. Results show that aggregate retention and embedment depth depend on aggregate-emulsion interaction, whereas rutting depends on the type of aggregate. Proper selection of aggregate and asphalt emulsion is important to maximize aggregate retention in chip seal. Chip loss also results from a lack of compatibility between the aggregate and asphalt emulsion. Results indicate that retention of aggregate depends on the prevailing charges of aggregate and emulsion particles. Moisture condition of the aggregate does not have any effect on chip loss. A new sweep test machine has been developed to assess chip loss, and it was found to be better than the sweep test currently recommended by the American Society for Testing and Materials (ASTM).
Keywords: Chip Seal; Lightweight Aggregate; Engineering, Civil (0543)